1885 Or.§Laws 263-64, An Act to Incorporate the City of Junction and Repeal An Act Entitled "An Act to Incorporate the City of Junction;" approved October 20, 1872, § 6. - (:unkn) unknown (My University, 1885)
[The] Mayor and common council . . . shall have exclusive power within the corporate limits of said city§. . . to regulate . . . the discharge of firearms or other preparation of gunpowder or combustibles of any kind[.]
Keywords: DISCHARGE; GUNPOWDER - STORAGE